Preparation method of pitch-based porous carbon with adjustable pore volume ratio as well as product and application of pitch-based porous carbon
By fully hydrolyzing and uniformly mixing the cellulose with alkali/urea/water solution system in asphalt-based porous carbon materials, combined with preoxidation and crosslinking, precarbonization and activation treatment, asphalt-based porous carbon with adjustable pore volume ratio was prepared, which solved the problems of insufficient strength of the material framework and unsuitable pore structure, and significantly improved the electrochemical performance of the material.
Patent Information
- Application Number
- CN202411785554.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing asphalt-based porous carbon materials have insufficient skeleton strength and the pore structure size is not suitable for silane deposition, which affects the material's cyclicity and charge and discharge efficiency.
The cellulose is fully hydrolyzed by alkali/urea/water solution system, and the asphalt is mixed evenly. After preoxidation and crosslinking, precarbonization and activation treatment, asphalt-based porous carbon with adjustable pore volume ratio is prepared.
The particle strength of asphalt-based porous carbon is significantly improved, the ratio of micropores and mesoporous is adjusted, the uniformity and electrochemical performance of silane deposition are enhanced, and the cycle stability and first-time Coulomb efficiency of lithium-ion batteries are improved.
Smart Images

Figure CN119612489A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation method of asphalt-based porous carbon with adjustable pore volume ratio, and a product and application thereof. Background Art
[0002] Porous carbon is considered to be one of the most promising carbon materials due to its well-developed internal pores. It has been widely used in the preparation of deposited silicon-carbon negative electrode materials. The development of highly economical porous carbon products is very attractive to existing scientific research fields and enterprises. Asphalt is a cheap petrochemical by-product and has a high potential for porous carbon production.
[0003] Asphalt molecules contain a large number of conjugated structures, which are easy to form graphite-like structures during carbonization, reducing the skeleton strength of asphalt porous carbon and failing to meet the production requirements of deposited silicon-carbon negative electrodes. In addition, the pore structure size of porous carbon seriously affects the uniformity of silane deposition. For example, a Chinese patent document with application publication number CN118206115A discloses a high-performance asphalt-based porous carbon material and a preparation method thereof, the method comprising: step one, mixing coal tar and carbon nanotubes to obtain a precursor; step two, pre-treating and crushing the precursor; step three, adding graphene and drying; step four, pre-oxidation treatment; step five, carbonization and activation treatment. This technical solution prepares porous carbon by adopting the processes of pre-oxidation, carbonization, and activation, and carbon nanotubes and graphene are also added as modifiers, and finally porous carbon particles with higher hardness are obtained. However, the preparation price of graphene and carbon nanotubes is relatively high, and large-scale mass production is difficult. In addition, there is a problem of uneven physical mixing of carbon materials during the addition process, which leads to large fluctuations in local pore distribution during activation, affecting the efficiency and uniformity of silane deposition.
[0004] Therefore, in order to improve the cyclability of deposited silicon-carbon negative electrode materials and alleviate the volume expansion of silicon, it is urgent to solve the problem of coordinated cooperation between the skeleton strength and pore structure of asphalt-based porous carbon particles. Summary of the invention
[0005] In response to the above problems, the present invention discloses a method for preparing asphalt-based porous carbon with adjustable pore volume ratio. The prepared asphalt-based porous carbon has extremely high particle strength, and the microporosity and micro-mesopore ratio are adjustable. The silicon-carbon negative electrode material prepared with it as the base has excellent cycle stability, high reversible specific capacity and first coulombic efficiency.
[0006] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing asphalt-based porous carbon with adjustable pore volume ratio, comprising:
[0008] S1: cellulose is dissolved in an alkali / urea / water solution and fully hydrolyzed to obtain a uniform solution, then asphalt is added, mixed fully, and then heated and dried to obtain a cellulose@asphalt composite material;
[0009] S2: heating the cellulose@asphalt composite material for pre-oxidation and cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material;
[0010] S3: activating the carbonized material to obtain asphalt-based porous carbon with adjustable pore volume ratio.
[0011] The present invention uses an alkali / urea / water solution system to fully hydrolyze cellulose to prepare a uniform solution for sufficient mixing with asphalt powder, thereby uniformly introducing cellulose long chains into the asphalt matrix. The cellulose is then used as a structural reinforcer and cross-linking agent for the asphalt matrix for carbonization treatment, which significantly improves the particle strength of the finally prepared asphalt-based porous carbon, thereby effectively resisting the charge and discharge expansion of silicon nanoparticles.
[0012] In an optional embodiment, step S1 includes at least one of the following features (1) to (7):
[0013] (1) The base is selected from one or more of LiOH, NaOH, and KOH;
[0014] Optionally, the base is selected from LiOH and NaOH; further optionally, the base is selected from LiOH.
[0015] (2) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000;
[0016] Optionally, the cellulose is selected from α-cellulose and / or β-cellulose;
[0017] Optionally, the number average molecular weight of the fiber is 5000-15000; further optionally, the number average molecular weight is 10000-15000.
[0018] (3) The mass ratio of cellulose, alkali, urea and water is (0.1-2.0):(0.2-5.0):3:(1-10);
[0019] Optionally, the mass ratio of cellulose, alkali, urea and water is (0.5-1.5):(0.5-2.0):3:(4-8);
[0020] Further optionally, the mass ratio of cellulose, alkali, urea and water is (1.0-1.5):(0.5-2.0):3:6.
[0021] (4) preparing the uniform solution at a low temperature of -20 to -10°C;
[0022] (5) The asphalt is in powder form with a particle size of D 50 2~8μm, D max ≤50μm;
[0023] Optionally, the asphalt is selected from conventional types in the art, such as petroleum asphalt, coal asphalt, mesophase asphalt, naphthalene asphalt, etc.; further optionally, the asphalt is selected from petroleum asphalt or coal asphalt.
[0024] (6) The mass ratio of cellulose to asphalt is 1:(5-20);
[0025] Optionally, the mass ratio of cellulose to asphalt is 1:(5-10).
[0026] (7) The heating and drying process has a temperature of 60 to 90°C.
[0027] The purpose of the drying is to remove the solvent in the system to obtain a fully mixed composite solid.
[0028] In an optional embodiment, in step S2:
[0029] Pre-oxidation cross-linking, on the one hand, produces cross-links between asphalt molecules, and on the other hand, produces additional cross-links between cellulose molecules and asphalt molecules through bridging oxygen, thereby forming a double cross-linked structure, which together improves the overall strength of the material; pre-oxidation cross-linking can also decompose and remove urea in the raw materials.
[0030] Optionally, the pre-oxidation cross-linking is performed at a temperature of 250-350°C.
[0031] Optionally, the pre-oxidation cross-linking time is 1 to 5 hours.
[0032] Optionally, the pre-oxidation cross-linking has a heating rate of 0.5 to 10° C. / min.
[0033] Optionally, the pre-oxidation cross-linking is carried out in a rotary kiln, the air flow rate is controlled to be 0.5 to 10 L / min, and the rotation speed of the rotary kiln is controlled to be 5 to 10 rpm.
[0034] Optionally, the protective atmosphere used in the pre-carbonization treatment includes one or more of nitrogen, argon and helium.
[0035] The alkali evenly dispersed in the cellulose@asphalt composite material also has a certain activation function, and the residual alkali during the pre-carbonization treatment also pre-activates the carbon material.
[0036] Optionally, the pre-carbonization treatment is performed at a temperature of 600 to 800°C;
[0037] Optionally, the pre-carbonization treatment is carried out for 4 to 10 hours.
[0038] Optionally, the pre-carbonization treatment has a heating rate of 0.5 to 20° C. / min.
[0039] In an optional embodiment, in step S3, the activation treatment comprises at least one of the following features (a) to (d):
[0040] (a) the activation treatment is selected from physical activation, and the activating agent is selected from one or more of CO, CO2, water vapor, and oxygen;
[0041] Optionally, the activating agent is selected from one or more of CO, CO2, and water vapor.
[0042] (b) The activation treatment is performed at a temperature of 700 to 1000° C.;
[0043] Optionally, the temperature is 800-900°C.
[0044] (c) the activation treatment lasts for 2 to 15 hours;
[0045] (d) In the activation treatment, the flow rate of the activating agent is 0.01 to 10 kg / h.
[0046] Optionally, in the activation treatment, the flow rate of the activating agent is 0.1 to 5.0 kg / h.
[0047] Optionally, the activation treatment has a heating rate of 0.5 to 20° C. / min.
[0048] Optionally, the activation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 0.5-10 rpm.
[0049] In a second aspect, the present invention also provides a pitch-based porous carbon with adjustable pore volume ratio prepared according to the above method, wherein the particle strength is not less than 4.6 GPa, the microporosity is 85-90%, and the micro-mesopore ratio is 4-7.
[0050] In a third aspect, the present invention also provides a method for preparing a silicon-carbon negative electrode material, which is prepared by using the asphalt-based porous carbon with adjustable pore volume ratio as a substrate and sequentially performing silicon deposition and carbon coating.
[0051] In an optional embodiment, the silicon deposition comprises at least one of the following features (1) to (7):
[0052] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0053] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0054] (2) The flow rate of the raw gas is 1 to 50 L / h;
[0055] (3) The silicon is deposited at a temperature of 300 to 800° C.;
[0056] (4) The silicon deposition time is 1 to 40 hours;
[0057] (5) The raw material gas also includes a carrier gas;
[0058] (6) The carrier gas is selected from nitrogen and / or argon;
[0059] (7) Based on the total volume of the raw gas being 100%, the volume proportion of the carrier gas is 1 to 30%.
[0060] In an optional embodiment, the carbon coating comprises at least one of the following features (1) to (6):
[0061] (1) The carbon coating adopts a raw material gas including a carbon-containing gas;
[0062] (2) the carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes;
[0063] Optionally, the C1-C4 alkane is selected from methane, ethane, propane, and butane; optionally, the C2-C4 olefin is selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkyne is selected from acetylene, propyne, and butyne.
[0064] (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h;
[0065] (4) The carbon coating is performed at a temperature of 400 to 1200° C.;
[0066] (5) The carbon coating time is 1 to 10 hours;
[0067] (6) The carbon-coated raw gas also includes an inert gas.
[0068] Optionally, the inert gas is selected from conventional types in the art, such as nitrogen, argon, etc.
[0069] In a fourth aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method.
[0070] In a fifth aspect, the present invention further provides a lithium-ion battery comprising the above-mentioned silicon-carbon negative electrode material.
[0071] Compared with the prior art, the present invention has the following beneficial results:
[0072] The invention discloses a method for preparing asphalt-based porous carbon with adjustable pore volume ratio, wherein cellulose is fully hydrolyzed with an alkali / urea / water solution system to prepare a uniform solution for sufficient mixing with asphalt powder, thereby uniformly introducing cellulose long chains into the asphalt matrix, and then the cellulose is used as a structural reinforcing agent and cross-linking agent for the asphalt matrix for carbonization treatment, which significantly improves the particle strength of the finally prepared asphalt-based porous carbon, thereby effectively resisting the charge and discharge expansion of silicon nanoparticles; a small amount of alkali contained in the raw material liquid can be used as an activation seed to pre-activate the carbon material and participate in the subsequent physical activation process, thereby improving the activation efficiency; at the same time, the presence of the alkali increases the microporosity, and the synergistic effect with the physical activation can accurately control the micropore and mesopore ratio in the asphalt-based porous carbon, thereby enhancing the adaptability to the subsequent silane deposition process; in addition, since the metal elements in the alkali exist inside the porous carbon pores and are in close contact with the deposited nano-silicon interface, the content of irreversible lithium in the battery charge and discharge is effectively reduced, and the first coulomb efficiency of the negative electrode material is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a structural diagram of the α-cellulose used in Example 1. DETAILED DESCRIPTION
[0074] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0075] In the description of the present invention, it should be noted that, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances. Below, according to the overall structure of the present invention, its embodiments are described. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.
[0076] In a first aspect, the present invention provides a method for preparing asphalt-based porous carbon with adjustable pore volume ratio, comprising:
[0077] S1: cellulose is dissolved in an alkali / urea / water solution and fully hydrolyzed to obtain a uniform solution, then asphalt is added, mixed fully, and then heated and dried to obtain a cellulose@asphalt composite material;
[0078] S2: heating the cellulose@asphalt composite material for pre-oxidation and cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material;
[0079] S3: activating the carbonized material to obtain asphalt-based porous carbon with adjustable pore volume ratio.
[0080] The present invention uses an alkali / urea / water solution system to fully hydrolyze cellulose to prepare a uniform solution for sufficient mixing with asphalt powder, thereby uniformly introducing cellulose long chains into the asphalt matrix. The cellulose is then used as a structural reinforcer and cross-linking agent for the asphalt matrix for carbonization treatment, which significantly improves the particle strength of the finally prepared asphalt-based porous carbon, thereby effectively resisting the charge and discharge expansion of silicon nanoparticles.
[0081] In an optional embodiment, step S1 includes at least one of the following features (1) to (7):
[0082] (1) The base is selected from one or more of LiOH, NaOH, and KOH;
[0083] Optionally, the base is selected from LiOH and NaOH; further optionally, the base is selected from LiOH.
[0084] (2) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000;
[0085] Optionally, the cellulose is selected from α-cellulose and / or β-cellulose;
[0086] The experiment found that compared with α-cellulose, β-cellulose and microcrystalline cellulose, the solution viscosity of carboxymethyl cellulose is higher, the uniformity of liquid phase mixing is lower, and the particle strength of the prepared asphalt-based porous carbon is slightly reduced.
[0087] Further optionally, the cellulose is selected from α-cellulose.
[0088] The number average molecular weight of the cellulose may specifically be 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, 13000, 14000, 15000 or any value within the above range; optionally, the number average molecular weight of the fiber is 5000-15000; further optionally, the number average molecular weight is 10000-15000.
[0089] It was found through experiments that the particle strength of the prepared pitch-based porous carbon is related to the number average molecular weight of the cellulose used.
[0090] (3) The mass ratio of cellulose, alkali, urea and water is (0.1-2.0):(0.2-5.0):3:(1-10);
[0091] Optionally, the mass ratio of cellulose, alkali, urea and water is (0.5-1.5):(0.5-2.0):3:(4-8);
[0092] Further optionally, the mass ratio of cellulose, alkali, urea and water is (1.0-1.5):(0.5-2.0):3:6.
[0093] It was found through experiments that with the optimization of the mass ratio of the above raw materials, the particle strength of the prepared asphalt-based porous carbon is higher.
[0094] (4) The uniform solution is prepared at a low temperature of -20 to -10°C; specifically, the temperature may be -20°C, -19°C, -18°C, -17°C, -16°C, -15°C, -14°C, -13°C, -12°C, -11°C, -10°C or any value within the above range.
[0095] (5) The asphalt is in powder form with a particle size of D 50 2 to 8 μm, specifically 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm or any value within the above range; D max ≤50μm, specifically can be 0.1μm, 0.5μm, 1μm, 2μm, 4μm, 3μm, 4μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm or any value within the above range.
[0096] Optionally, the asphalt is selected from conventional types in the art, such as petroleum asphalt, coal asphalt, mesophase asphalt, naphthalene asphalt, etc.; further optionally, the asphalt is selected from petroleum asphalt or coal asphalt.
[0097] (6) The mass ratio of cellulose to asphalt is 1:(5-20); specifically, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or any ratio within the above range; optionally, the mass ratio of cellulose to asphalt is 1:(5-10).
[0098] Experiments have shown that with the optimization of the mass ratio of cellulose to asphalt, the particle strength of the prepared asphalt-based porous carbon is higher.
[0099] (7) The heating and drying temperature is 60-90°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value within the above range.
[0100] The purpose of the drying is to remove the solvent in the system to obtain a fully mixed composite solid.
[0101] In an optional embodiment, in step S2:
[0102] Pre-oxidation cross-linking, on the one hand, produces cross-links between asphalt molecules, and on the other hand, produces additional cross-links between cellulose molecules and asphalt molecules through bridging oxygen, thereby forming a double cross-linked structure, which together improves the overall strength of the material; pre-oxidation cross-linking can also decompose and remove urea in the raw materials.
[0103] Optionally, the pre-oxidation cross-linking temperature is 250-350°C, specifically 250°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or any value within the above range.
[0104] Optionally, the pre-oxidation cross-linking time is 1 to 5 hours, specifically 1 hour, 1.5 hours, 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours or any value within the above range.
[0105] Optionally, the pre-oxidation cross-linking has a heating rate of 0.5 to 10°C / min, specifically 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the above range.
[0106] Optionally, the pre-oxidation cross-linking is carried out in a rotary kiln, and the air flow rate is controlled to be 0.5-10 L / min, specifically 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min or any value within the above range; the rotation speed of the rotary kiln is controlled to be 5-10 rpm, specifically 5 rpm, 6 rpm, 7 rpm, 8 rpm, 9 rpm, 10 rpm or any value within the above range.
[0107] Optionally, the protective atmosphere used in the pre-carbonization treatment includes one or more of nitrogen, argon and helium.
[0108] The alkali evenly dispersed in the cellulose@asphalt composite material also has a certain activation function, and the residual alkali during the pre-carbonization treatment also pre-activates the carbon material.
[0109] Optionally, the pre-carbonization treatment is carried out at a temperature of 600-800°C, specifically 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C or any value within the above range.
[0110] Optionally, the pre-carbonization treatment time is 4 to 10 h, specifically 4.0 h, 4.5 h, 5.0 h, 5.5 h, 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10 h or any value within the above range.
[0111] Optionally, the pre-carbonization treatment has a heating rate of 0.5 to 20°C / min, specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 15°C / min, 20°C / min or any value within the above range.
[0112] In an optional embodiment, in step S3, the activation treatment comprises at least one of the following features (a) to (d):
[0113] (a) the activation treatment is selected from physical activation, and the activating agent is selected from one or more of CO, CO2, water vapor, and oxygen;
[0114] Optionally, the activating agent is selected from one or more of CO, CO2, and water vapor.
[0115] (b) The activation treatment is carried out at a temperature of 700-1000°C, specifically 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 950°C, 1000°C or any value within the above range; optionally, the temperature is 800-900°C.
[0116] (c) The activation treatment is performed for 2 to 15 hours, specifically 2 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or any value within the above range.
[0117] (d) In the activation treatment, the flow rate of the activator is 0.01 to 10 kg / h, specifically 0.01 kg / h, 0.05 kg / h, 0.1 kg / h, 0.5 kg / h, 1 kg / h, 1.5 kg / h, 2 kg / h, 2.5 kg / h, 3 kg / h, 3.5 kg / h, 4 kg / h, 4.5 kg / h, 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h, 10 kg / h or any value within the above range; optionally, in the activation treatment, the flow rate of the activator is 0.1 to 5.0 kg / h.
[0118] Optionally, the activation treatment has a heating rate of 0.5 to 20°C / min, specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min or any value within the above range.
[0119] Optionally, the activation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 0.5-10rpm, specifically 0.5rpm, 1rpm, 2rpm, 3rpm, 4rpm, 5rpm, 6rpm, 7rpm, 8rpm, 9rpm, 10rpm or any value within the above range.
[0120] In a second aspect, the present invention also provides a pitch-based porous carbon with adjustable pore volume ratio prepared according to the above method, wherein the particle strength is not less than 4.6 GPa, the microporosity is 85-90%, and the micro-mesopore ratio is 4-7.
[0121] In a third aspect, the present invention also provides a method for preparing a silicon-carbon negative electrode material, which is prepared by using the asphalt-based porous carbon with adjustable pore volume ratio as a substrate and sequentially performing silicon deposition and carbon coating.
[0122] In an optional embodiment, the silicon deposition comprises at least one of the following features (1) to (7):
[0123] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0124] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0125] (2) The flow rate of the raw gas is 1 to 50 L / h, specifically 1 L / h, 2 L / h, 3 L / h, 5 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h, 30 L / h, 35 L / h, 40 L / h, 45 L / h, 50 L / h or any value within the above range;
[0126] (3) The silicon deposition temperature is 300-800°C, specifically 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value within the above range.
[0127] (4) The silicon deposition time is 1 to 40 hours, specifically 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours or any value within the above range.
[0128] (5) The raw material gas also includes a carrier gas;
[0129] (6) The carrier gas is selected from nitrogen and / or argon;
[0130] (7) Taking the total volume of the raw gas as 100%, the volume proportion of the carrier gas is 1 to 30%, specifically 1%, 5%, 8%, 10%, 15%, 18%, 20%, 25%, 28%, 30% or any value within the above range.
[0131] In an optional embodiment, the carbon coating comprises at least one of the following features (1) to (6):
[0132] (1) The carbon coating adopts a raw material gas including a carbon-containing gas;
[0133] (2) the carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes;
[0134] Optionally, the C1-C4 alkane is selected from methane, ethane, propane, and butane; optionally, the C2-C4 olefin is selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkyne is selected from acetylene, propyne, and butyne.
[0135] (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h, specifically 1 L / h, 2 L / h, 3 L / h, 4 L / h, 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h, 10 L / h or any value within the above range.
[0136] (4) The carbon coating has a temperature of 400-1200°C, specifically 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value within the above range.
[0137] (5) The carbon coating time is 1 to 10 hours, specifically 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or any value within the above range.
[0138] (6) The carbon-coated raw gas also includes an inert gas.
[0139] Optionally, the inert gas is selected from conventional types in the art, such as nitrogen, argon, etc.
[0140] In a fourth aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method.
[0141] In a fifth aspect, the present invention further provides a lithium-ion battery comprising the above-mentioned silicon-carbon negative electrode material.
[0142] Example 1
[0143] S1. At -15°C, 10 kg of α-cellulose (number average molecular weight 12000) was dissolved in a LiOH / urea / water solution (the mass ratio of LiOH, urea and water was 10 kg: 30 kg: 60 kg). A uniform solution was obtained under strong stirring. 100 kg of particle size D 50 Powdered petroleum asphalt with a size of 5 μm was added into a uniform solution, and the mixture was stirred and mixed for 10 hours and then dried at 80°C to obtain a cellulose@asphalt composite material;
[0144] S2. Place 50 kg of cellulose@asphalt composite material in a tubular furnace, introduce air at a flow rate of 5 L / min, heat to 300°C at 5°C / min and keep warm for 4 hours to pre-oxidize the asphalt and remove urea, then switch to nitrogen. When the oxygen content drops below 50 ppm, heat to 700°C at 5°C / min for 6 hours to pre-carbonize and pre-activate the composite material to obtain a pre-carbonized material;
[0145] S3. Place 30 kg of the above pre-carbonized material in a rotary furnace, set the rotation rate to 5 r / min, raise the temperature to 800°C at 10°C / min for steam activation to obtain asphalt-based porous carbon, the steam flow rate is 1.0 kg / h, and the activation time is 9 hours.
[0146] Example 2
[0147] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of LiOH added is replaced with 5 kg.
[0148] Example 3
[0149] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added LiOH is replaced with 20 kg.
[0150] Example 4
[0151] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added α-cellulose is replaced with 5 kg.
[0152] Example 5
[0153] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added α-cellulose is replaced with 15 kg.
[0154] Example 6
[0155] The preparation process is substantially the same as that of Example 1, except that in step S1, LiOH is replaced with an equal mass of NaOH.
[0156] Example 7
[0157] The preparation process is substantially the same as that of Example 1, except that in step S1, α-cellulose is replaced with an equal mass of carboxymethyl cellulose (number average molecular weight of 2200).
[0158] Example 8
[0159] The preparation process is substantially the same as that of Example 1, except that in step S1, α-cellulose is replaced with an equal mass of β-cellulose (number average molecular weight of 5000).
[0160] Comparative Example 1
[0161] 50kg of particle size D 50 Powdered petroleum asphalt with a particle size of 5 μm was placed in a tubular furnace, and air with a flow rate of 5 L / min was introduced. The temperature was raised to 300°C at a rate of 5°C / min and kept at this temperature for 4 hours to achieve pre-oxidation of the asphalt. Then, nitrogen was switched. When the oxygen content dropped below 50 ppm, the temperature was raised to 700°C at a rate of 5°C / min for 6 hours to achieve pre-carbonization, and a pre-carbonized material was obtained.
[0162] 30 kg of the above pre-carbonized material was placed in a rotary furnace, the rotation rate was set to 5 r / min, and the temperature was raised to 800°C at 10°C / min for steam activation to obtain asphalt-based porous carbon. The steam flow rate was 1.0 kg / h and the activation time was 9 h.
[0163] Comparative Example 2
[0164] S1. At -15°C, 10 kg of waterborne epoxy resin (Shanghai Guangyan Chemical Technology Co., Ltd., brand: 618, model: ZZZF04031) was dissolved in 60 kg of aqueous solution, and a uniform solution was obtained under strong stirring. 100 kg of particle size D 50 Powdered petroleum asphalt with a size of 5 μm was added to the above solution, and the mixture was stirred for 10 hours and then dried at 80° C. to obtain an epoxy resin@asphalt composite material.
[0165] Steps S2 to S3 are exactly the same as those in Example 1.
[0166] Comparative Example 3
[0167] The preparation process is substantially the same as that of Example 1, except that in step S1, LiOH is not added.
[0168] The performance data of the asphalt-based porous carbon prepared in each embodiment and comparative example are listed in the following Table 1, wherein the specific surface area and pore distribution are obtained by a precise high-precision nitrogen adsorption and desorption test system. During the strength test of the particles, particles of similar particle size are selected and measured by a strength tester.
[0169] Table 1
[0170]
[0171] Comparing Examples 1 to 3 and Comparative Example 3 in Table 1, the comprehensive physical indexes of the asphalt-based porous carbon prepared in Example 1 are good, and the comprehensive electrochemical performance is excellent; the microporosity, micro-mesopore ratio and particle strength of the asphalt-based porous carbon prepared in Example 2 slightly decrease with the decrease of the amount of LiOH used; the microporosity, micro-mesopore ratio and particle strength of the asphalt-based porous carbon prepared in Example 3 slightly increase with the increase of the amount of LiOH used. In Comparative Example 3 where LiOH is not added, the particle strength of the prepared asphalt-based porous carbon is significantly reduced because α-cellulose cannot be dissolved, and there is no alkali-assisted activation, resulting in a significant decrease in the micropore content of the prepared porous carbon.
[0172] Comparing Examples 1 and 4-5, the particle strength of the asphalt-based porous carbon prepared in Example 4 decreases with the decrease of cellulose content, and the particle strength of the asphalt-based porous carbon prepared in Example 5 increases with the increase of cellulose content; the microporosity and micro-mesopore ratio of the asphalt-based porous carbon prepared by both are not significantly different from those in Example 1.
[0173] Comparing Examples 1 and 6, in Example 6, sodium hydroxide was used as a base instead of lithium hydroxide, and the particle strength of the prepared asphalt-based porous carbon decreased, and the microporosity and micro-mesopore ratio also decreased; this may be because compared with lithium hydroxide, sodium hydroxide will cause insufficient dissociation of cellulose and is not conducive to the formation of micropores.
[0174] Comparing Examples 1 and 7-8, the particle strength of the asphalt-based porous carbon prepared in Example 7 is slightly lower than that in Example 1. This may be due to the higher viscosity of the carboxymethyl cellulose solution and the low uniformity of liquid phase mixing, which leads to a decrease in the particle strength of the asphalt-based porous carbon. The particle strength of the asphalt-based porous carbon prepared in Example 8 is also slightly lower than that in Example 1. This may be due to the lower number average molecular weight of cellulose than that in Example 1.
[0175] Comparing Example 1 with Comparative Examples 1-2, in Comparative Example 1, no cellulose was added, and the particle strength of the prepared asphalt-based porous carbon was extremely low; in Comparative Example 2, other common reinforcing agent epoxy resin was used instead of cellulose, and the reinforcing effect was not ideal.
[0176] Application Examples
[0177] 10kg of asphalt-based porous carbon prepared in each embodiment and comparative example was placed in a rotary kiln as a substrate, and a raw gas composed of monosilane gas and nitrogen was introduced at 500°C, the raw gas flow rate was 8L / h, nitrogen accounted for 2% in the raw gas, and the deposition time was 30h. The carbon coating process is to put the above silicon-carbon material into a rotary kiln, introduce acetylene gas, and carry out the process under nitrogen protection and high temperature of 700°C, the acetylene gas flow rate is 8L / h, and the carbon coating time is 5h.
[0178] The products prepared in each embodiment and each comparative example are used as negative electrode materials to assemble batteries.
[0179] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.
[0180] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the final product prepared in each embodiment and each comparative example was added as the negative electrode active material and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).
[0181] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.
[0182] (3) Assembly of lithium-ion batteries
[0183] Using PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an aluminum plastic shell package, and dried at 100°C under a relative vacuum pressure of -0.95×105Pa until the moisture content is less than 100ppm. The electrolyte is injected into the dried bare battery cell, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and the package, static, formation (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaping, and capacity testing (capacity division) are performed to make a soft-pack liquid lithium-ion battery. When assembling the battery, five batteries are prepared for each test, and a total of five groups of data are tested. The final performance takes the average value of the five groups of data.
[0184] The battery cycle performance was tested on a blue-electric device, specifically: at 25°C, first discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles. The expansion test is obtained by disassembling the battery after the battery cycle and comparing the thickness of the electrode before and after the cycle. The specific test / calculation results are shown in Table 2 below.
[0185] Table 2
[0186]
[0187] Comparing Examples 1 to 8 in Table 2, the silicon-carbon negative electrode materials prepared in each example have excellent cycle stability and low expansion rate, but the electrochemical performance of the product prepared in Example 1 is the best. Due to slight differences in parameters such as the pore volume, microporosity, and micro-mesopore ratio of the porous carbon substrate itself, the reversible specific capacity, first efficiency, cycle retention rate, expansion rate, etc. of the silicon-carbon negative electrode materials prepared in other examples are slightly different.
[0188] Comparing Example 1 with Comparative Examples 1-2, the silicon-carbon negative electrode materials prepared in Comparative Examples 1-2 respectively have poor cycle stability and large expansion rate, which is related to the low particle strength of the porous carbon substrate itself.
[0189] Comparing Example 1 with Comparative Example 3, the capacity, retention rate and first efficiency of the silicon-carbon negative electrode material prepared in Comparative Example 3 are significantly reduced, and the expansion rate is significantly increased, which is related to the low pore volume and low micro-mesopore ratio of the porous carbon substrate itself.
[0190] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing asphalt-based porous carbon with adjustable pore volume ratio, characterized in that: include: S1: cellulose is dissolved in an alkali / urea / water solution and fully hydrolyzed to obtain a uniform solution, then asphalt is added, mixed fully, and then heated and dried to obtain a cellulose@asphalt composite material; S2: heating the cellulose@asphalt composite material for pre-oxidation and cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material; S3: activating the carbonized material to obtain asphalt-based porous carbon with adjustable pore volume ratio.
2. The method for preparing asphalt-based porous carbon with adjustable pore volume ratio according to claim 1, characterized in that: Step S1 includes at least one of the following features (1) to (7): (1) The base is selected from one or more of LiOH, NaOH, and KOH; (2) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000; (3) The mass ratio of cellulose, alkali, urea and water is (0.1-2.0):(0.2-5.0):3:(1-10); (4) preparing the uniform solution at a low temperature of -20 to -10°C; (5) The asphalt is in powder form with a particle size of D 50 2~8μm, D max ≤50μm; (6) The mass ratio of cellulose to asphalt is 1:(5-20); (7) The heating and drying process has a temperature of 60 to 90°C.
3. The method for preparing pitch-based porous carbon with adjustable pore volume ratio according to claim 1, characterized in that: In step S2: The pre-oxidation cross-linking is carried out at a temperature of 250 to 350° C. and a time of 1 to 5 hours; The pre-carbonization treatment uses a protective atmosphere including one or more of nitrogen, argon and helium, a temperature of 600 to 800° C., and a time of 4 to 10 hours.
4. The method for preparing asphalt-based porous carbon with adjustable pore volume ratio according to claim 1, characterized in that: In step S3, the activation treatment includes at least one of the following features (a) to (d): (a) the activation treatment is selected from physical activation, and the activating agent is selected from one or more of CO, CO2, water vapor, and oxygen; (b) The activation treatment is performed at a temperature of 700 to 1000° C.; (c) the activation treatment lasts for 2 to 15 hours; (d) In the activation treatment, the flow rate of the activating agent is 0.01 to 10 kg / h.
5. A pitch-based porous carbon with adjustable pore volume ratio prepared by the method according to any one of claims 1 to 4, characterized in that: The particle strength is not less than 4.5 GPa, the microporosity is 85-90%, and the micro-mesopore ratio is 4-7.
6. A method for preparing a silicon-carbon negative electrode material, characterized in that: The asphalt-based porous carbon with adjustable pore volume ratio as claimed in claim 6 is used as a substrate, and silicon deposition and carbon coating are performed in sequence to prepare the product.
7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The silicon deposition comprises at least one of the following features (1) to (7): (1) The raw material gas used in the silicon deposition includes a silicon source gas; (2) The flow rate of the raw gas is 1 to 50 L / h; (3) The silicon is deposited at a temperature of 300 to 800° C.; (4) The silicon deposition time is 1 to 40 hours; (5) The raw material gas also includes a carrier gas; (6) The carrier gas is selected from nitrogen and / or argon; (7) Based on the total volume of the raw gas being 100%, the volume proportion of the carrier gas is 1 to 30%.
8. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The carbon coating comprises at least one of the following features (1) to (6): (1) The raw material gas used in the carbon coating includes a carbon-containing gas; (2) The carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h; (4) The carbon coating is performed at a temperature of 400 to 1200° C.; (5) The carbon coating time is 1 to 10 hours; (6) The carbon-coated raw gas also includes an inert gas.
9. A silicon-carbon negative electrode material prepared according to the method according to any one of claims 6 to 8.
10. A lithium ion battery, characterized in that: Comprising the silicon-carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Silicon-based negative electrode material and preparation method thereof
CN116914112A
High-performance asphalt-based porous carbon material and preparation method thereof
CN118206115A
Heteroatom-doped porous hard carbon negative electrode material and preparation method and application thereof
CN118289737A
KR20240163123A
Cited By
Porous carbon and preparation method therefor
WO2026086002A1